Decoding how the older adults identify misinformation: an analysis of internal mechanisms - Zhaotong Wu; Yepei Wang; Hui Yan (Information Research: An International Electronic Journal)
Introduction. This study aims to explore the key factors influencing misinformation recognition among older adults, understand the internal mechanisms of how they identify misinformation, and ultimately promote age-friendly improvements in the information environment of the AI era.